The Evolution of an Optic Nerve Head Granuloma Due to Sarcoidosis. (3rd March 2016) - Hickman, S. J.; Quhill, F.; Pepper, I. M.
ABSTRACT: Sarcoidosis can affect the optic nerves by means of optic disc oedema secondary to posterior uveitis, optic disc oedema secondary to raised intracranial pressure, optic neuritis, optic atrophy secondary to compression or infiltration from a primary central nervous system lesion, and primary granuloma of the optic nerve head. The authors report the use of optical coherence tomography in assessing the response to immunosuppression in a 57-year-old woman with an optic nerve head granuloma.